2020
DOI: 10.3390/cells9041031
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of NNK, A Tobacco Smoke Carcinogen, on the miRNA and Mismatch DNA Repair Expression Profiles in Lung and Head and Neck Squamous Cancer Cells

Abstract: Tobacco smoking is a common risk factor for lung cancer and head and neck cancer. Molecular changes such as deregulation of miRNA expression have been linked to tobacco smoking in both types of cancer. Dysfunction of the Mismatch DNA repair (MMR) mechanism has also been associated with a poor prognosis of these cancers, while a cross-talk between specific miRNAs and MMR genes has been previously proposed. We hypothesized that exposure of lung and head and neck squamous cancer cells (NCI and FaDu, respectively)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 84 publications
7
41
0
Order By: Relevance
“…At present, several studies have identified sets of miRNAs specific for different tumors, including lung cancer, mesothelioma, bladder cancer, colorectal cancer, glioblastoma multiforme, oral cancer, uveal melanoma, hematological malignancies, etc. [137][138][139][140][141][142][143][144].…”
Section: Micrornas (Mirnas or Mirs)mentioning
confidence: 99%
“…At present, several studies have identified sets of miRNAs specific for different tumors, including lung cancer, mesothelioma, bladder cancer, colorectal cancer, glioblastoma multiforme, oral cancer, uveal melanoma, hematological malignancies, etc. [137][138][139][140][141][142][143][144].…”
Section: Micrornas (Mirnas or Mirs)mentioning
confidence: 99%
“…Instead, we found out that the smoking was likely to increase TMB/MSI, another two approved biomarkers for immunotherapy response, consequently increasing the response to immunotherapy (Figure 1F,1G). Supporting this notion, recent evidence also revealed the association between heavy smoking and TMB (26)(27)(28) and MSI (29,30) in the corresponding tumors (Figure 1), since clinical trialbased evidence has demonstrated that TMB is linked to the pathological response to ICIs (18). Despite this, TMB is complex, and its related data are not available in real-time for decision-making in the first-line setting.…”
Section: Biomarkers Predicting Responses To Immunotherapymentioning
confidence: 89%
“…Direct enzyme-linked immunosorbent assay (ELISA) was performed to quantify the protein expression levels of cytoplasmic p-EGFR (Tyr 1092), and nuclear NF- κ B (p65) and p-STAT3 (Tyr 705), in experimental and control treated-HCs, as previously described and in Supplementary Materials [ 90 ].…”
Section: Methodsmentioning
confidence: 99%